Analisis Perbandingan Kualitas User Experience Platform E-Wallet Ovo dan Dana Menggunakan Metode UX Honeycomb dan System Usability Scale - Idil Arfandi; Hendra Mesra (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze and compare the quality of user experience between two popular e-wallet platforms in Indonesia, OVO and DANA, using the UX Honeycomb method and the System Usability Scale (SUS). The UX Honeycomb method evaluates six key aspects of user experience: useful, usable, desirable, findable, accessible, and credible. Meanwhile, the SUS method measures system usability from the users’ perspective. The respondents in this study were students of Hasanuddin University who actively use both platforms. The results indicate that both OVO and DANA exhibit good usability levels based on SUS scores. However, differences were found in several UX Honeycomb dimensions. DANA scored higher in credibility and findability, while OVO performed better in usability and desirability. These findings provide valuable insights for app developers to enhance user experience quality and serve as a reference for users in choosing an e-wallet platform that suits their preferences.